Voting for structures: knowing art & molecular innovations for pharmacists-in-training / Ibtisam Abdul Wahab - Abdul Wahab, Ibtisam (2023)
Pharmacy students or the pharmacists-in-training (PIT), were given examples of diversified molec-ular structures with various biological functions during their introductory pharmaceutical organ-ic chemistry course. These molecules would consist of glucose, cholesterol, and penicillin, among others (Nahar et al. 2019). Infinitene (mo-lecular formula: C48H24), the Molecule of the Year 2021, was also introduced to the PIT as a helically twisted, figure-eight compound-look (Figure 1). This was celebrated as an innovation in synthetic chemistry, to produce such structure of an infinity (¥)-shaped entity. The molecule is a non-planar aromatic carbon atoms system with a twisted or looped framework (Krzeszewski et al. 2022; Orozco-Ic, et al. 2022). The chemistry lessons were delivered at the lecture hall after a two-year hiatus, due to the COVID-19 pandemic.